Comparison of the effectiveness of Bach flower therapy and music therapy on dental anxiety in pediatric patients: A randomized controlled study - Uma B Dixit; Rishita R Jasani (Wolters Kluwer Medknow Publications, 2020)
Background: Dental anxiety is a primary cause of missed dental appointments, delayed treatment, and untreated dental caries in children. Alternative techniques such as music therapy (MT) and Bach flower therapy (BFT) have potential to reduce anxiety. Lack of randomized controlled studies evaluating effectiveness of these methods in reducing dental anxiety led us to this study. Aim: To compare the effectiveness of BFT and MT on reduction of dental anxiety in pediatric patients. Materials and Methods: A total of 120 children (aged 4-6 years) were selected and randomly allocated to three groups: BFT, MT, and control. All children received oral prophylaxis and fluoride treatment. Dental anxiety was evaluated using North Carolina Behavior Rating Scale, Facial Image Scale (FIS), and physiological parameters. Results: Significantly better behavior was seen in children from the BFT group as compared to the control group (P = 0.014). FIS scores measured postoperatively did not show significant differences among the groups. Children from the BFT and MT groups showed a significant decrease in the pulse rates intraoperatively from the preoperative period. Intraoperative systolic blood pressure in children from the MT group was significantly lower than both the BFT and the control groups. Diastolic blood pressure significantly increased in the control group intraoperatively, whereas other groups showed a decrease. Conclusion: The results of this study demonstrate significant effects of both single dose of BFT and exposure to MT, on reduction of dental anxiety in children aged between 4 and 6 years.